Pengendalian Proyek Dengan Menggunakan Metode Crash Program (Studi Kasus Pembangunan Bendungan Bulango Ulu Paket 1, Item Pekejaan Maindam, Provinsi Gorontalo) - Mudatsir; Arfan Usman Sumaga; Mohammad Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The implementation of infrastructure development in Indonesia has grown rapidly in recent years, particularly in the context of its status as a developing country. One major project receiving attention in Gorontalo Province is the construction of the Bulango Ulu Dam. However, this project has faced delays in completion, which necessitates an in-depth analysis to optimize both time and cost. This study aims to analyze the project’s work network to identify the critical path and evaluate time and cost efficiency through the application of a crash program using additional overtime hours. The research was conducted at several project locations: Tulova Village, Owata Village, and Mongiilo Village in Bone Bolango Regency, Gorontalo Province. The study employed the crash program method and utilized Microsoft Project and Microsoft Excel for data processing. These tools supported the identification of critical tasks and the analysis of overtime productivity, crash duration, cost slope, and post-crash program time and cost efficiency. The analysis revealed that critical tasks in the Bulango Ulu Dam construction include drilling and grouting, stockpile work, dam top miscellaneous work, cleaning, and jetty trash boom installation. Time efficiency resulting from overtime additions was found to be: 10% (1 hour), 16.90% (2 hours), 22.62% (3 hours), 26.67% (4 hours), and 30% (5 hours). Meanwhile, cost efficiency peaked at 2.58% with 4 hours of overtime. These findings suggest that the optimal scenario for time and cost efficiency in hoarding work is achieved by adding 4 hours of overtime.